2014
DOI: 10.1186/s40169-014-0037-y
|View full text |Cite
|
Sign up to set email alerts
|

Unique expression features of cancer‐type organic anion transporting polypeptide 1B3 mRNA expression in human colon and lung cancers

Abstract: Background We have previously identified the cancer-type organic anion transporting polypeptide 1B3 (Ct-OATP1B3) mRNA in several human colon and lung cancer tissues. Ct-OATP1B3 is a variant of the liver-type OATP1B3 (Lt-OATP1B3) mRNA, which is a hepatocyte plasma membrane transporter with broad substrate specificity. However, in cancer tissues, both the detailed characteristics of Ct-OATP1B3 mRNA expression and its biological functions remain unclear. With this point in mind, we sought to characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 31 publications
1
24
0
Order By: Relevance
“…While OATP1B3 is predominantly expressed in liver under normal conditions, it has been detected in various malignant tissues including tumors of the cervix, intestines, liver, lung, pancreas, and genitourinary tract (Lancaster et al, 2013). A cancer-specific form of OATP1B3, also referred to as cancertype OATP1B3, has been identified in which an alternative splice site is used, resulting in a protein that is structurally different from that found in normal liver; the cancer-specific OATP1B3 transcript has been detected in malignant tissues from the colon (Nagai et al, 2012;Han et al, 2013;Thakkar et al, 2013;Sun et al, 2014), pancreas (Han et al, 2013;Thakkar et al, 2013), and lung (Nagai et al, 2012;Sun et al, 2014). Some commonly used detection methods for wild-type OATP1B3 do not detect this cancer-specific OATP1B3; therefore, studies that do not show expression of OATP1B3 in cancerous tissues must be interpreted with caution if they did not search for the cancer-specific variant (Evangeli et al, 2017).…”
Section: Oatp Expression In Tumor Tissues and Theirmentioning
confidence: 99%
See 1 more Smart Citation
“…While OATP1B3 is predominantly expressed in liver under normal conditions, it has been detected in various malignant tissues including tumors of the cervix, intestines, liver, lung, pancreas, and genitourinary tract (Lancaster et al, 2013). A cancer-specific form of OATP1B3, also referred to as cancertype OATP1B3, has been identified in which an alternative splice site is used, resulting in a protein that is structurally different from that found in normal liver; the cancer-specific OATP1B3 transcript has been detected in malignant tissues from the colon (Nagai et al, 2012;Han et al, 2013;Thakkar et al, 2013;Sun et al, 2014), pancreas (Han et al, 2013;Thakkar et al, 2013), and lung (Nagai et al, 2012;Sun et al, 2014). Some commonly used detection methods for wild-type OATP1B3 do not detect this cancer-specific OATP1B3; therefore, studies that do not show expression of OATP1B3 in cancerous tissues must be interpreted with caution if they did not search for the cancer-specific variant (Evangeli et al, 2017).…”
Section: Oatp Expression In Tumor Tissues and Theirmentioning
confidence: 99%
“…Some commonly used detection methods for wild-type OATP1B3 do not detect this cancer-specific OATP1B3; therefore, studies that do not show expression of OATP1B3 in cancerous tissues must be interpreted with caution if they did not search for the cancer-specific variant (Evangeli et al, 2017). The transport function of the cancer-specific OATP1B3 variant for at least some substrates is significantly decreased or abolished (Thakkar et al, 2013;Sun et al, 2014), although transport of other substrates is similar to that of the wild-type transporter (Imai et al, 2013).…”
Section: Oatp Expression In Tumor Tissues and Theirmentioning
confidence: 99%
“…For OATP1B1 expression in hepatocellular carcinoma, some studies reported increased expression while one reported unchanged compared to control [ 104 , 105 , 106 ]. Recently, a cancer-type OATP1B3 mRNA was identified in cancer cell lines and tissues from lung, colon and pancreatic origin [ 107 , 108 , 109 ]. Compared to wild-type OATP1B3 that is highly expressed in the liver, the cancer-type OATP1B3 lacks an N-terminus encoding region.…”
Section: Altered Expression Of Oatp1b1 and 1b3 In Pathological Conmentioning
confidence: 99%
“…Novel SLCO1B3 variants were identified in cancerous tissues. A cancer-type variant with a distinct 5′region, termed cancer-type (ct)- SLCO1B3 coding for the cancer-type (ct)-OATP1B3 transporter was identified as the main OATP1B3 variant in colon, lung (Sun et al, 2014 ) pancreatic (Thakkar et al, 2013 ), and also ovarian cancer (Alam et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%